Sex differences in comorbidity at diagnosis of multiple sclerosis: A population-based study. (5th April 2016) - Marrie, Ruth Ann; Patten, Scott B.; Tremlett, Helen; Wolfson, Christina; Warren, Sharon; Svenson, Lawrence W.; Jette, Nathalie; Fisk, John
Abstract : Objective: To determine the prevalence of comorbidity in the multiple sclerosis (MS) population at the time of MS diagnosis. We also compared the prevalence of comorbidity in the MS population to that in a matched cohort from the general population. Methods: Using population-based administrative health data from 4 Canadian provinces, we identified 23, 382 incident MS cases and 116, 638 age-, sex-, and geographically matched controls. We estimated the prevalence of hypertension, diabetes, hyperlipidemia, heart disease, chronic lung disease, epilepsy, fibromyalgia, inflammatory bowel disease, depression, anxiety, bipolar disorder, and schizophrenia at MS diagnosis using validated case definitions. We compared the populations using rate ratios. Results: Of the MS cases, 16, 803 (71.9%) were female. The most prevalent comorbidity was depression (19.1%). Compared to the matched population, all comorbidities except hyperlipidemia were more common in the MS population. Relative to the matched populations, the prevalence of hypertension was 16% higher for women with MS and 48% higher for men with MS, thus there was a disproportionately higher prevalence of hypertension in men with MS than women. Men with MS also had a disproportionately higher prevalence than women with MS for diabetes, epilepsy, depression, and anxiety. Conclusions: Comorbidity is more common than expected in MS, even around the time of diagnosis. The prevalence of psychiatric comorbidity is particularly high and highlights the need for clinical attention to this issue. The observed sex-specific differences in the burden of comorbidity in MS, which differ from those in the matched population, warrant further investigation.